PENGUATAN KARAKTER GEMAR MEMBACA MURID KELAS III MELALUI GERAKAN LITERASI DI SD NEGERI 14 MASALIMA DESA PAMMAS KECAMATAN LIUKANG KALMAS KABUPATEN PANGKEP - Safitri, Hilda; Tarman; Saeful, Muhammad (Almeera Education, 2025)
This study aims to describe the role of the teacher in strengthening the character of reading in class III students through the school literacy movement at SD Negeri 14 Masalima. The method used is descriptive analysis method using data collection techniques namely observation, interviews and documentation. The research results are as follows: strengthening the character of fond of reading, strengthening curiosity, planning, implementing, and evaluating GLS, program implementation has reached 3 stages, namely the habituation, development, and learning stages. The obstacles are: Some students' motivation to read is still low, lack of initiative in students to read, lack of collection of books in the reading corner, books in the reading corner are rarely replaced and there are still some students who are still not fluent in reading. The solution to solving the problem is by motivating students, guiding and directing students, providing good facilities (infrastructure),